Transforming Local Knowledge(s) into European Recommendations: A Methodological Approach to Co-Creating Policy Briefs for Educational Inclusion - Sofia Almeida Santos; Mariana Fonseca; Ana Cristina Torres; Eunice Macedo; Amélia Veiga (Social Sciences)
This article explores the process of developing policy briefs (PB) as strategic tools to translate knowledge stemming from the analysis of local educational practices into inclusive European policy recommendations. This paper highlights how educational practices from eleven partner institutions across Denmark, Norway, Poland, Portugal, and Spain informed recommendations to prevent early leaving from education and training (ELET) and to enhance youth’s school engagement. Educational practices involved a collaborative dialogue among multi-stakeholders to establish a shared vision about educational inclusion, and the co-creation of educational practices supported by monitoring, evidence collection, and the identification of promising examples. These elements reflect the aim to embed educational inclusion in policy development, while underscoring the role of PBs as mechanisms of participatory knowledge transfer between countries and sectors, bringing together diverse voices from policymakers, educators, researchers, and young people. In doing so, the methodological approach to produce PB recognised local produced knowledge as a catalyst for informed decisions promoting quality education. The analysis of PB highlights elements of the identified educational practices addressing ELET challenges, such as (i) implementing co-creation methodologies in both educational contexts and political formulation; (ii) addressing student citizenship as central to meaningful learning; (iii) valuing cross-sector partnerships to address systemic challenges, and (iv) reinforce relational pedagogies that enhance student–teacher and student–student relationships.